Quantum collapse as a source of the seeds of cosmic structure during the radiation era - Leon, Gabriel (2014)
The emergence of the seeds of cosmic structure, from a perfect isotropic and homogeneous Universe, has not been clearly explained by the standard version of inflationary models as the dynamics involved preserve the homogeneity and isotropy at all times. A proposal that attempts to deal with this problem, by introducing "the self-induced collapse hypothesis," has been introduced by D. Sudarsky and collaborators in previous papers. In all these works, the collapse of the wave function of the inflaton mode is restricted to occur during the inflationary period. In this paper, we analyze the possibility that the collapse happens during the radiation era. A viable model can be constructed under the condition that the inflaton field variable must be affected by the collapse while the momentum variable can or cannot be affected. Another condition to be fulfilled is that the time of collapse must be independent of k . However, when comparing with recent observational data, the predictions of the model cannot be distinguished from the ones provided by the standard inflationary scenario. The main reason for this arises from the requirement that primordial power spectrum obtained for the radiation era matches the amplitude of scalar fluctuations consistent with the latest cosmic microwave background observations. This latter constraint results in a limit on the possible times of collapse and ensures that the contribution of the inflaton field to the energy-momentum tensor is negligible compared to the contribution of the radiation fields.